Healthcare Workers' Experiences and Views of Using Surgical Masks and Respirators, and Their Attitudes on the Sustainability: A Semi-Structured Survey Study during COVID-19 - Anu Venesoja; Kaisa Grönman; Susanna Tella; Salla Hiltunen; Krista Koljonen; Svetlana Butylina; Laura Rotinen; Paulus Torkki; Katri Laatikainen (MDPI AG, 2021)
A universal mask use was instituted in healthcare during COVID-19 pandemic in 2020. The extensive growth in the consumption of surgical masks and respirators brought new challenges. Healthcare workers had to get accustomed to wearing the facemasks continuously, raising concerns on the patient, occupational, and environmental safety. The aim of this study is to describe frontline healthcare workers and other authorities' views and experiences on continuous use of surgical masks and respirators (facemasks) and their attitudes towards environmental and sustainability issues. A cross-sectional web-based survey was conducted in Finland during the COVID-19 pandemic in autumn 2020. The respondents(N = 120) were recruited via social media, and the data were collected using a purpose-designed questionnaire. Descriptive statistics and inductive content analysis were used to analyze the quantitative data and qualitative data, respectively. The healthcare workers perceived their own and patient safety, and comfortability of facemasks as important, but according to their experiences, these properties were not evident with the current facemasks. They considered protection properties more important than environmental values. However, biodegradability and biobased material were seen as desired properties in facemasks. Based on the results, the current facemasks do not meet users' expectations well enough. Especially the design, breathability, and sustainability issues should be taken more into account.